1996
DOI: 10.1093/bja/76.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative infusion of amino acids prevents postoperative hypothermia

Abstract: Intraoperative infusion of amino acids has been found to stimulate energy expenditure and thereby prevent anaesthesia-induced hypothermia. Rectal temperature and respiratory gas exchange were measured in 24 female patients before and after isoflurane anaesthesia. Sixteen patients had an amino acid mixture of 240 kJ h-1, infused over 1-2 h before anaesthesia and eight control patients received saline. We compared the results with data from six female volunteers treated with amino acids; they were not premedicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 0 publications
3
37
1
Order By: Relevance
“…In previous studies [3,5], the thermogenesis effect of intraoperative amino acid infusion has been obvious from about 2 h after the induction of anesthesia, just as in our results, but few studies have investigated the relationship between the doses of amino acids administration during operations and the thermogenesis effect. This study showed that from 100 and 120 min after skin incision to 6 h after the operation, medium and high doses of amino acid infusion had the same effect in preventing hypothermia, while low doses of amino acids had no such effect, as Sahin et al [9] found before.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In previous studies [3,5], the thermogenesis effect of intraoperative amino acid infusion has been obvious from about 2 h after the induction of anesthesia, just as in our results, but few studies have investigated the relationship between the doses of amino acids administration during operations and the thermogenesis effect. This study showed that from 100 and 120 min after skin incision to 6 h after the operation, medium and high doses of amino acid infusion had the same effect in preventing hypothermia, while low doses of amino acids had no such effect, as Sahin et al [9] found before.…”
Section: Discussionsupporting
confidence: 75%
“…Intraoperative amino acid infusion exerts a marked thermogenic effect with enhanced oxygen consumption [2,3,4,5], mainly in the extra-splanchnic tissues, and significantly attenuates the decrease in core temperature during general anesthesia [6,7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the most frequently used nutrients are amino acids. It was noted that amino acid solution administered 1–2 h before general anesthesia induction and at the first hour of the maintenance of anesthesia as 240 kj/h has been suggested to increase heat accumulation and prevent hypothermia by delaying heat generation stimulation and to increase vasoconstriction threshold, and that postoperative shivering were not observed [1821]. In addition, when amino acid solution was administered to patients under spinal anesthesia, central temperature increased before performing spinal anesthesia and the decrease in central temperature reduced after performing it [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Selldén, one of authors of this article, reported that infusion of amino acids before or during general anesthesia is useful to prevent hypothermia [27]. In addition, amino acids infusion was demonstrated to shorten hospital stay [2].…”
Section: Prevention Of Hypothermiamentioning
confidence: 94%